The Challenges of Prior Use to New Zealand Registered Trade Mark Law - Batty, Rob (Victoria University of Wellington Law Review, 2014)
Under the Trade Marks Act 2002, the registrant of a trade mark is provided with the exclusive rights to use its trade mark. Priority to such exclusive rights is awarded to the person who files a trade mark application first. A searchable Register of trade marks enables traders and the public to see which trade marks have already been registered and by whom. This seemingly certain system is complicated by the continuing relevance of unregistered trade marks under New Zealand law. The first user of a trade mark in the marketplace is considered the true "owner" or "proprietor" of a trade mark. A prior user of an unregistered mark is able to prevent registration of a trade mark, or cancel an existing trade mark registration, even when the application was filed in ignorance of any prior use and where there is no prospect of consumer confusion. This article explores the unsatisfactory nature and consequences of this law of "proprietorship" and questions its continuing relevance.